Involvement of plasma membrane H+‐ATPase in the ammonium‐nutrition response of barley roots. Issue 6 (27th September 2018) - Zhang, Maoxing; Ding, Ming; Xu, Feiyun; Afzal, Muhammad Rahil; Chen, Xi; Zeng, Houqing; Yan, Feng; Zhu, Yiyong
Abstract: Barley ( Hordeum vulgare L.) is a typical ammonium ( NH 4 + )‐sensitive crop species and exhibits a futile‐ NH 4 + efflux from root cells. Plasma membrane (PM) H + ‐ATPase is responsible for pumping H + out of plant cells and providing the driving force for the transport of various substances. We hypothesized that PM H + ‐ATPase is involved in this NH 4 + efflux process of barley roots. Barley plants were cultivated in hydroponic solution with 1.0 mM NH 4 + or 1.0 mM nitrate ( NO 3 - ) as the sole nitrogen source. Plasma membrane vesicles were isolated from the root tips for analyses of the activity. Plasma membrane H + ‐ATPase was tested by Western Blot. The transcription of PM H + ‐ATPase genes was analyzed using qRT‐PCR. Proton and NH 4 + efflux from barley roots was analyzed by scanning ion‐selective electrode technique. The results show that root and shoot growth was repressed by NH 4 + nutrition when compared to NO 3 - nutrition. Plasma membrane H + ‐ATPase activity of barley roots under NH 4 + nutrition was significantly higher than that under NO 3 - nutrition. Methyl‐ammonium (MeA), a non‐metabolizable analog of NH 4 +, had no significant effect on PM H + ‐ATPase activity. The enhanced PM H + ‐ATPase activity by NH 4 + nutrition was consistent with a higher abundance of PM H + ‐ATPase protein and higher transcription levels of six PM H + ‐ATPase genes. By using the pharmacological agents vanadate and fusicoccin, a close linkage was observed between H + efflux and NH 4 + efflux from barley roots. Taken together, NH 4 + nutrition stimulates PM H + ‐ATPase activity, and this stimulation is possibly triggered by NH 4 + assimilation in barley roots. NH 4 + efflux from barley roots is associated with PM H + ‐ATPase activity which could provide the driving force for NH 4 + efflux. Ammonium efflux might be considered as a disposal strategy in barley roots which prevents NH 4 + overloading the root cytoplasm.